CBMT-02. UP-REGULATION OF Γ-GLUTAMYL-TRANSFERASE CAN BE USED TO IMAGE GLIOBLASTOMA USING HYPERPOLARIZED Γ-GLUTAMYL-[1-13C]GLYCINE MRS. (11th November 2019) - Batsios, Georgios; Najac, Chloe; Cao, Peng; Viswanath, Pavithra; Subramani, Elavarasan; Saito, Yutaro; Marie Gillespie, Anne; Yoshihara, Hikari; Larson, Peder; Sando, Shinsuke; Ronen, Sabrina
Abstract: γ-glutamyl-transferase (GGT) is a key enzyme in the γ-glutamyl cycle, which regulates glutathione homeostasis. The enzyme is localized on the outer cell membrane and cleaves glutathione to glutamate and cysteinylglycine. As such, it facilitates uptake of the amino acids essential for intracellular synthesis of glutathione (GSH), which is the major thiol anti-oxidant. GGT is upregulated in glioblastoma, but remains low in normal brain. It is therefore an attractive molecular imaging target for specific detection of glioblastoma. The goal of our study was therefore to assess for the first time the value of hyperpolarized (HP) γ-glutamyl-[1- 13 C]glycine (γ-Glu-[1- 13 C]Gly) for imaging glioblastoma in orthotopic tumor-bearing rats. Athymic nude rats with U87 glioblastoma tumors or tumor-free controls were investigated. First, we confirmed that GGT expression was significantly higher in U87 tumors compared to normal rat brain tissue. GSH levels were also higher. Imaging studies were then performed by injecting HP γ-Glu-[1- 13 C]Gly and acquiring dynamic 13 C MR spectra using a flyback spectral-spatial slab sequence on a preclinical Bruker 3T MR system. The dynamic data were analyzed by measuring the signal-to-noise (SNR) ratios of the substrate (γ-Glu-[1- 13 C]Gly) and the product ([1- 13 C]Glycine). Comparison of control and tumor-bearing rats showed no statistically significant difference in the SNR of the substrate. In contrast, the SNR of the product demonstrated a significantly higher level of HP [1- 13 C]Glycine in the tumor-bearing rats compared to controls. Consistent with the higher levels of HP [1- 13 C]Glycine, the [1- 13 C]Gly-to-γ-Glu-[1- 13 C]Glycine ratio was also significantly higher in tumor-bearing animals relative to controls (0.046±0.004 vs 0.021±0.008 respectively; p=0.03). Further studies are needed to assess the generality of our findings. Nonetheless, this study demonstrates for the first time the feasibility of using γ-Glu-[1- 13 C]Gly to monitor GGT activity and thus could serve as a new approach for monitoring the presence of tumor.